COAL PETROLOGY AND THE ORIGIN OF COAL MACERALS: A WAY AHEAD? - Scott A.C. (My University, 2002)
The development of coal petrology and the establishment of a nomenclatural system have proved of major use both for the industrial utilization of coal and for the development of a broad understanding of coal formation and diagenesis. The development, over the past 30 years, however, of nomenclature that includes aspects of plant origin and process is a retrograde step (e.g. pyrofusinite, degradofusinite, and funginite). Equally problematic is the use of prescriptive formulae to indicate coal ‘origins’. This paper reviews some of the problems involved with coal petrology as it is usually practiced. In addition, new advances in organic geochemical techniques have led to a fuller understanding of the relationship of plants and coal macerals. Recent research on the origin of coal macerals is presented and there is a discussion of the problems and challenges facing coal petrologists. A holistic approach to studies of the origin of coal and coal macerals, which includes not only petrographic but also chemical and biological studies, is advocated.